Simulation-based assessments of fire emergency preparedness and response in virtual reality - Kwegyir-Afful Ebo; Hassan Tajudeen Ola; Kantola Jussi (TAYLOR & FRANCIS LTD, 2022)
The current study aimed at evaluating the prospects of a three-dimensional gas power plant (GPP) simulation in an immersive virtual reality (IVR) environment for fire emergency preparedness and response (EPR). To achieve this aim, the study assessed the possibility of safety situational awareness, evacuation drills and hazard mitigation exercises during a fire emergency simulation scenario. The study likewise evaluated the safety and ergonomics of the environment while addressing this aim. We employed the virtual reality accident causation model (VR-ACM) for the assessment with 54 participants individually in IVR. Participants were grouped into two according to whether they had work experience in engineering or not. The obtained results suggested that IVR can be realistic and safe, with the potential for presenting hazardous scenarios necessary for fire EPR. Furthermore, the results indicated that there were no statistically significant differences in the perceptions of both groups regarding the prospects of IVR towards EPR.